(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2005)
A palynological study of the Nayband Formation (central eastern Iran) has been carried out in order to review and update its stratigraphic framework. In its type locality the formation crops out on the southern flank of Nayband Mountain, about 200 km south of Tabas. It consists of a thick, mixed siliciclastic-carbonate sequence subdivided into four members; in ascending order: the Gelkan Member (mainly shales and silstones), the Bidestan Member (marls, siltstones with minor sandstones and fossiliferous limestones), the Howz-e-Sheikh Member (sandstones and siltstones), and the Howz-e-Khan Member (sponge and coral dominated reefs alternating with marls and sandstones). Three palynological assemblages have been recognised; in ascending order: a) an assemblage characterised by the presence of Annulispora folliculosa and A. microannulata which allows the Gelkan Member and most of the Bidestan Member to be assigned an early Norian age; (b) an assemblage marked by the first occurrence of Polycingulatisporites mooniensis, which indicates the upper part of the Bidestan Member is mid-late Norian; c) an assemblage containing Classopollis chateaunovi in association with Retitriletes austroclavatidites, Gliscopollis meyeriana, Limbosporites lundbladii, Rugaletes awakinoensis and Callialasporites dampieri that allows the Howz-e-Sheikh Member to be assigned a Rhaetian age. The presence of some Eurasian and/or cosmopolitan forms in the Rhaetian microflora reflects the position of the Iranian plate on the southern margin of Eurasia.